Pachelbels d-Moll-Ciacona als strukturelles Vorbild für eine Aemulatio - Paech, Katharina Larissa (De musica disserenda, 2010)
Many musicologists have discussed the influence of Buxtehude's ostinato compositions on Johann Sebastian Bach's Passacaglia in C minor, BWV 582. But Johann Pachelbel's Ciacona in D minor seems to have had a much stronger effect on it: this piece served as the model for the structure of the Passacaglia.
Keywords: Pachelbel, Johann, 1653-1706; "Ciacona in d"; Bach, Johann Sebastian, 1685-1750; "Passacaglia c-Moll BWV 582"; orgelska glasba; 17./18.st.